2018
DOI: 10.1172/jci.insight.122795
|View full text |Cite
|
Sign up to set email alerts
|

Long-term remission despite clonal expansion of replication-competent HIV-1 isolates

Abstract: Clonal expansion of T cells harboring replication-competent virus has recently been demonstrated in patients on suppressive antiretroviral therapy (ART) regimens. However, there has not been direct evidence of this phenomenon in settings of natural control, including in posttreatment controllers who maintain control of viral replication after treatment when ART is discontinued. We present a case of an individual who has had undetectable viral loads for more than 15 years following the cessation of ART. Using n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 47 publications
5
41
0
Order By: Relevance
“…Further, there was no increase in the proportion of escaped or unrecognized epitopes seen over time in the defective proviruses of controllers on ART. Large proviral clones were observed in controllers on ART, as reported in treatment-naive controllers (62). The proportion of proviruses found in large clones was similar to that of chronic progressors.…”
Section: Study Participantssupporting
confidence: 70%
See 1 more Smart Citation
“…Further, there was no increase in the proportion of escaped or unrecognized epitopes seen over time in the defective proviruses of controllers on ART. Large proviral clones were observed in controllers on ART, as reported in treatment-naive controllers (62). The proportion of proviruses found in large clones was similar to that of chronic progressors.…”
Section: Study Participantssupporting
confidence: 70%
“…Controllers on ART have clonally expanded cells harboring HIV-1 proviruses, as has been shown in controllers who are ART naive (Figure 7, A-C, and refs. 52,62). Furthermore, the proportions of proviruses that are observed in clones in controllers on ART are similar to the proportions seen in chronic progressors on ART and, as with chronic progressors, the proportions observed in clones increases over time on ART ( Figure 7C), suggesting that the mechanisms driving clonal proliferation of infected cells in people on ART are not greatly altered by strong HIV-1-specific CTL responses.…”
Section: Discussionsupporting
confidence: 52%
“…These results argued against viral escape or CTL dysfunction as mechanisms by which these reservoirs were not eliminated ex vivo and led us to propose that reservoir-harboring cells from ARTsuppressed individuals are resistant to elimination by CTLs (22). Of note, a separate study has recently shown that virus derived from clonally expanded HIV-infected cells from antiretroviraltreated (ARV-treated) individuals often remains sensitive to autologous CTL, further arguing against epitope escape as a dominant mechanism underlying the persistence of these cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of an env gene means that there is only a single cycle of infection which is very different from the exponential infection that occurs with a replication-competent virus. However, we have seen comparable levels of CD8+ T cell mediated inhibition of cells infected with pseudotyped virus and replication-competent isolates from patients (Veenhuis et al, 2018) and we may have seen even better levels of inhibition if Env epitopes were expressed on infected cells. While this assay does not measure direct killing of infected CD4+ T cells, we and others have shown that direct contact between CD8+ T cells and target CD4+ T cells is needed for suppression (Saez-Cirion et al, 2007;Veenhuis et al, 2018) and we show here that direct contact between ES3 target cells and NK and CD8+ T cells is needed to reduce viral transcription (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 55%
“…The suppression assay used here has been previously described for CD8+ T cell and NK cell mediated suppression (Walker-Sperling et al, 2017;Veenhuis et al, 2018;Kwaa et al, 2019). It is based on an assay described by Saez-Cirion et al (2007) but differs in that the CD4+ T cells are not activated prior to infection.…”
Section: Resultsmentioning
confidence: 99%